Sociability, Social Capital, and Community Development - Cook, Ian Gillespie. author. aut Link
IX, 140 p. 2 illus.
Keywords: This book provides a critical understanding of contemporary issues within a global society and how these relate to eight case study examples (The Netherlands, UK, USA, China, India, South Africa, Bangladesh, and Japan). The authors draw on their rich and diverse experience to explore four major themes of contemporary relevance: overall aging of societies; governance and institutions; emergency services and public health provisions; and community activism and involvement. The key issues within the book - sociability, social capital, and community development - are examined in the context of an increasingly aging world population. The authors' sense of optimism is linked to growing evidence that community activism is on the rise and can effectively plug the gap between public need and provision of service. Ian G. Cook is Emeritus Professor of Human Geography at Liverpool John Moores University. Jamie P. Halsall is Senior Lecturer in Social Sciences at the University of Huddersfield. Paresh Wankhade is Professor of Leadership and Management at Edge Hill University. “Drawing from examples from across the world, this book argues for a recognition of the role of cooperation and sociability in addressing the public health challenges of the 21st century. This volume provides a welcome optimistic perspective on humanity’s future, focusing on what can be achieved when communities work together. It does not provide easy answers, but rather sheds light on possible avenues for alternative, more equitable futures.” Katie Willis, Professor of Human Geography, Royal Holloway, University of London.